Unprecedented multifunctionality of grubbs and hoveyda–grubbs catalysts: Competitive isomerization, hydrogenation, silylation and metathesis occurring in solution and on solid phase - Martinez Amezaga, Maitena (2017)
This contribution showcases the interplay of several non-metathetic reactions (isomerization, silylation and “hydrogen-free” reduction) with metathesis in systems comprising a functionalized olefin and a soluble or resin-immobilized silane. These competing, one-pot reactions occur under activation by second-generation Ru-alkylidene catalysts. Different olefinic substrates were used to study the influence of the substitution pattern on the reaction outcome. Emphasis is placed upon the rarely reported yet important transformations implying a solid phase-supported silane reagent. Catalytic species involved in and reaction pathways accounting for these concurrent processes are evidenced. An unexpected result of this research was the clearly proved partial binding of the olefin to the resin, thereby removing it from the reacting ensemble.